2010
DOI: 10.4103/0019-557x.75733
|View full text |Cite
|
Sign up to set email alerts
|

A review of tracking progress towards elimination of Iodine deficiency disorders in Tamil Nadu, India

Abstract: The total goiter rate of 13.5% and median urinary iodine excretion of 89.5 μg/L is indicative of iodine deficiency in Tamil Nadu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
0
14
1
Order By: Relevance
“…Taken as a whole, various studies across India have revealed a wide‐ranging prevalence of goitre of 1·5 to 44·5% . However, the most recent studies on the subject from well‐known authors in India reveal a goitre prevalence of 8·8% to 15·5% …”
Section: Discussionmentioning
confidence: 99%
“…Taken as a whole, various studies across India have revealed a wide‐ranging prevalence of goitre of 1·5 to 44·5% . However, the most recent studies on the subject from well‐known authors in India reveal a goitre prevalence of 8·8% to 15·5% …”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in Tamil Nadu region, 1230 children aged between 6 and 12 years were examined and the total rate of goitre was found to be 13.5% and the mean urinary iodine excretion was found to be 8.95 µg/dL which was low (25). In our study, the mean urinary iodine excretion was found to be 14.46±8.9 µg/dL which was higher compared to this study and severe iodine deficiency was found in 1.9% of the subjects (n=4), moderate iodine deficiency was found in 9.8% of the subjects (n=21) and mild iodine deficiency was found in 26.2% of the subjects (n=56).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys conducted in various states showed that no state in the country is free from IDD and revealed that out of 282 districts surveyed, IDD poses a major public health problem in 241 districts where the prevalence is more than 10%. 1,2,[4][5][6][7] The Government of India launched National Goiter Control Program (NGCP) in the year 1962 considering the burden of IDD in the country and renamed it as National Iodine Deficiency Disorders Control Program (NIDDCP) in the year 1992. Universal salt iodization was identified as the main strategy to eliminate IDD form India and was made mandatory in the year 1997.…”
mentioning
confidence: 99%